Relationship between healthy house and smoking habits with afb (+) pulmonary tuberculosis cases at the singotrunan public health center, Banyuwangi district - Fakhira, Amira Dhisa; Keman, Soedjajadi (Journal of Health Management and Pharmacy Exploration, 2024)
Singotrunan Public Health Center has 65 cases of AFB (+) pulmonary TB, which means increased by 22.6% from the previous year. Healthy house and smoking habits are known to be some of the risk factors for pulmonary TB cases. This study aims to analyze the relationship between healthy house and smoking habits with AFB (+) Pulmonary Tuberculosis cases in the working area of the Singotrunan Public Health Center, Banyuwangi District. The method used is analytic research with a case-control type. This research was conducted on 28 samples, consist of 14 from the case group and 14 from the control group in the working area of the Singotrunan Health Center. Data were obtained from assessments using observation sheets and interviews using questionnaires. The data obtained were analyzed univariably using tabulation and bivariably using the Chi Square test using the Odds Ratio value to determine the dynamics of the independent and dependent variables. The results of the Chi Square test showed that there is a significant relationship between healthy houses (pvalue = 0.022) and smoking habits (pvalue = 0.002) with AFB pulmonary TB cases (+). The Odds Ratio value shows that unhealthy homes have a 6.6 times higher risk and smoking increases the risk 15 times higher for being diagnosed with AFB (+) Pulmonary TB. In conclusion, healthy homes and smoking habits have the potential to increase the risk of AFB (+) Pulmonary TB in the working area of the Singotrunan Public Health Center, Banyuwangi District.